Hemorrhagic shock secondary to button battery ingestion - Takesaki, Naomi Andreia; Reis, Marcelo Conrado dos; Miranda, Maria Luisa Ferreira de; Baracat, Emílio Carlos Elias (São Paulo Medical Journal, 2014)
CONTEXT: Button battery ingestion is a frequent pediatric complaint. The serious complications resulting from accidental ingestion have increased significantly over the last two decades due to easy access to gadgets and electronic toys. Over recent years, the increasing use of lithium batteries of diameter 20 mm has brought new challenges, because these are more detrimental to the mucosa, compared with other types, with high morbidity and mortality. The clinical complaints, which are often nonspecific, may lead to delayed diagnosis, thereby increasing the risk of severe complications. CASE REPORT: A five-year-old boy who had been complaining of abdominal pain for ten days, was brought to the emergency service with a clinical condition of hematemesis that started two hours earlier. On admission, he presented pallor, tachycardia and hypotension. A plain abdominal x-ray produced an image suggestive of a button battery. Digestive endoscopy showed a deep ulcerated lesion in the esophagus without active bleeding. After this procedure, the patient presented profuse hematemesis and severe hypotension, followed by cardiorespiratory arrest, which was reversed. He then underwent emergency exploratory laparotomy and presented a new episode of cardiorespiratory arrest, which he did not survive. The battery was removed through rectal exploration. CONCLUSION: This case describes a fatal evolution of button battery ingestion with late diagnosis and severe associated injury of the digestive mucosa. A high level of clinical suspicion is essential for preventing this evolution. Preventive strategies are required, as well as health education, with warnings to parents, caregivers and healthcare professionals.